Rb4Li2TiOGe4O12: A Titanyl Nonlinear Optical Material with the Widest Transparency Range. Issue 50 (22nd October 2019) - Xia, Mingjun; Tang, Chuan; Li, Rukang
Abstract: Practical mid‐infrared (MIR) coherent light beams generated by frequency conversion in nonlinear optical (NLO) crystals are indispensable in time‐resolved infrared vibrational spectroscopy, remote light detection and ranging, and free‐space communications. Herein, a new titanyl germanate Rb4 Li2 TiOGe4 O12 (RLTG) MIR NLO crystal was obtained by heavier element substitution. It features a complicated structure network composed of compressed TiO5 square pyramids and distorted GeO4 tetrahedra, separated by Rb + and Li + cations. More importantly, RLTG exhibits concurrently short ultraviolet (0.28 μm) and long IR (5.58 μm) transmittance cutoffs, fully covering the atmospheric transparent window of 3–5 μm. Related to the short UV cutoff, it shows a higher laser‐induced damage threshold in comparison to commercial MIR NLO crystals, about twice that of KTiOPO4 (KTP) and 50 times that of AgGaS2 (AGS). Abstract : Crystal clear : A germanate Rb4 Li2 TiOGe4 O12 mid‐infrared (MIR) nonlinear optical (NLO) crystal, containing well‐aligned compressed TiO5 groups and distorted GeO4 tetrahedra, shows a strong second‐harmonic generation (SHG) response. It exhibits concurrently short ultraviolet and long IR cutoffs, fully covering the atmospheric window spectral range of 3–5 μm.